Re-positive PCR of SARS-CoV-2 in health care persons during COVID-19 pandemic - Alebouyeh, Masoud; Aavani, Pooya; Abdulrahman, Nareen Arif; Haleem, Azad Abduljabar; Karimi, Abdollah; Armin, Shahnaz; Fallah, Fatemeh; Amirali, Arezu; Sadr, Saeed; Ghandchi, Ghazaleh; Abdollahi, Nafiseh; Ghanaie, Roxana Mansour; et al. (Cellular and Molecular Biology, 2022)
Reinfection rate with SARS-CoV-2 and degree of protection by the induced antibody after the first episode of the infection is not well known, so it makes a big dilemma for health care personnel (HCP) who work in the front line of combating SARS-CoV-2. In this study, we investigated the frequency of SARS-CoV-2 redetection among HCP after the initial onset of the infection in a children’s hospital during one year. Out of 131 seropositive HCP, 13.7% of them were symptomatic and PCR positive during 74-360 days after first sampling. Analysis of demographic data of seropositive HCP showed a correlation between a higher number of family members, higher body mass index, and the existence of underlying diseases with SARS-CoV-2 redetection. In conclusion, reinfection is one of the important problems in the SARS-CoV-2 pandemic. Research on this topic can help us to find answers to questions for estimating the duration of human protection with produced immunity after the infection or vaccination.